Integrated oral health empowerment program for Imtaq Shighor Isy Karima Boarding School - Bramantoro, Taufan; Putra, Ramadhan Hardani; Firdausi, Nurul Layly; Muhammad, Azzamul Khoir; Silmah, Xanashova (Faculty of Dental Medicine Universitas Airlangga, 2024)
Background: A significant public health challenge among children and adolescents is dental and oral health problems, which is around 60-90%. This dental and oral disease can have a negative impact on the quality of life, causing pain, limited oral function, and emotional stress, and can cause students' teaching and learning activities to decline. Purpose: improving the health of students through early detection and independent and integrated management of general and dental health at Imtaq Shighor Isy Karima Islamic Boarding School, Karanganyar Regency, Central Java Province. Method: Socialization activity on general health and dental management of students carried out in August 2023 at Imtaq Shighor Isy Karima Boarding School, Karanganyar Regency, Central Java Province. There were 30 cottage caregivers as participants. Evaluation is carried out by giving a pretest and post-test. Result: Based on the evaluation results, it was found that the average pre-test score was 68.18 while the post-test average was 81.36 so participants experienced an increase in knowledge of 13.18%. Conclusion: participants who took part in socialization activities on early detection and management of general and dental health of students experienced increased knowledge and were active in discussions, based on the participants' pre-test and post-test completion.